The effectiveness of miniature media in improving junior high school students' learning outcomes in specific gravity - Suharyanto, Suharyanto; Kumalasari , Tety; Nevrita , Nevrita (ARKA INSTITUTE, 2025)
This study aims to analyze the effectiveness of using miniature kelong media in improving the learning outcomes of junior high school students on the subject of mass density. Miniature kelong is a local wisdom-based learning medium that represents the structure of traditional fishing gear in the coastal area of Bintan Regency. The study used a mixed methods approach with a quasi-experimental design involving two classes: an experimental class taught using miniature kelong media and a control class taught conventionally. Data were collected through pre-tests and post-tests, then analyzed using t-tests and normalized gain. The results showed that the average increase in learning outcomes (normalized gain) in the experimental class was much higher than in the control class. The t-test showed a significant difference between the two groups. These findings prove that the kelong miniature media is effective in improving student learning outcomes because it is able to present the abstract concept of density in a concrete, contextual, and meaningful way through a local cultural approach. The implications of this study support the integration of local wisdom in science learning to improve the quality of education in coastal areas.